Optimalisasi Hasil Pembelajaran: Penerapan Model Pembelajaran Jigsaw dalam Pendidikan Sejarah untuk Menganalisis Perjuangan Kemerdekaan Indonesia - Budiman, Moh. Arif (Progressive of Cognitive and Ability, 2023)
Low student activity in the learning process can affect student learning outcomes which do not comply with the minimum completeness criteria set by the school. To improve good learning activities aimed at processes, especially those that include good learning activities between teachers and students, it is necessary to use a jigsaw type cooperative learning approach. This research uses a quantitative approach to obtain data and analysis through reflective, participatory and collaborative studies. After carrying out classroom research actions, data can be obtained from the evaluation results of student learning activities through the 1st test, namely 68.30 (not yet using jigsaw type cooperative learning). After using the jigsaw, the evaluation results of student learning activities through tests increased to 77.00 in cycle I, 80.10 in cycle II and 82.90 in cycle III. Meanwhile, the percentage of students' classical learning completion level before using puzzles was 44.74%, after using puzzles it gradually increased from 71.05% in cycle I, 84.21% in cycle II and 97.37% in cycle III.